Peningkatan Produktivitas dan Pendapatan Petani Melalui Penerapan Model Pengelolaan Tanaman Terpadu Padi Sawah di Kabupaten Pesawaran, Lampung - Robet Asnawi (Jurnal Penelitian Pertanian Terapan, 2014)
One of maintain self-sufficiency is programs realized through the implementation of field school of integrated crops management (SLPTT) target increased quality rice with rice cultivation techniques, increased cropping intensity and productivity of rice. This research was conducted at SLPTT locations of Pesawaran regency (4 district), Lampung Province, from May until September 2010. The number of observed samples consisting of 180 units such as LL VUB (Field Laboratory of New Superior Variety) location is 60 units, LL non VUB location is 60 units and non SLPTT location is 60 units. The treatment applied SLPTT LL VUB is PTT (ICM) model such as superior verieties (Inpari 1, Inpari 7, Inpari 9 and Cigeulis), jajar legowo planting system (2:1 and 3:1), and site-specific fertilizer recommendation (Ministry Agriculture recommendation), and application pattern field school (PFS). At the SLPTT LL non VUB location, treatment applied was Ciherang variety and fertilizer dose of local farmers (specific location), while non SLPTT location adapted to the habits of farmers. Data collected were production cost, yield components, and farming system problems. The results showed that the average productivity of paddy at the SLPTT LL VUB location is 7.174 kg/ha, SLPTT non VUB 6.737 kg/ha and non SLPTT 4.587 kg/ha. Use of new superior varieties (VUB) increased productivity by 8,85% compared with SLPTT non VUB and 47,13% compared with non SLPTT. Farmer income in SLPTT LL VUB locations is Rp.17.410.000,-/ha (R/C=3,15), SLPTT LL non VUB location Rp.13.488.806,-/ha (R/C=2,46) and non SLPTT location Rp.9.885.625,-/ha (R/C=2,34). Through the application of VUB in SLPTT location can increase farmers' income 29,07% to 76,12%. Keywords: increasing, production, income, SLPTT, rice